Analisis Implementasi Kebijakan Pemberdayaan Usaha Kecil, Menengah dan Koperasi - Hendrikus Tri Wibawanto Gedeon (Center fo State Civil Apparatus Training and Development and Competency Mapping, 2006)
In order to strengthen grass-root economy, the Indonesian government has releaased Law No. 9 Year 1995 comprising policies particularly directed to empowering the country’s cooperatives and small-medium enterprises. However, in practice, hindrances occur and cause the failure in achieving the policies goals. This article tries to elaborate those hindrances. Furthermore, key factors based upon the theory of policy implementation are analyzed to shoot the problems so that future implementation of such policies is able to bring about the expected goals.